Re-appraisal of two fossil Frullaniaceae species (Marchantiophyta, Porellales) from the mid-Cretaceous Burmese amber. (August 2021) - Li, Ya; Li, Li-Qin; Feldberg, Kathrin; Wu, Peng-Cheng; Schneider, Harald; Schmidt, Alexander R.; Wang, Yong-Dong
Abstract: With more than 300 extant species, Frullaniaceae represent a species-rich clade of the predominantly epiphytic order Porellales, occurring in humid tropical and subtropical forests as well as temperate regions. Earliest fossils of Frullaniaceae are known from mid-Cretaceous Burmese and Alaskan ambers. So far, evidence for four or five fossil species have been recovered in these ambers. The steady search for new fossils is important, since many liverwort fossils lack important characters and sometimes only the investigation of numerous specimens can provide all relevant characters. Based on two newly discovered and exquisitely preserved gametophytes from mid-Cretaceous Burmese amber, we provide a detailed investigation and re-appraisal of two previously described species of Frullaniaceae, namely Frullania baerlocheri and Protofrullania cornigera . The new discovery of a complete gametophyte of F . baerlocheri with both vegetative and fertile parts enables an emended morphological description, and demonstrates that F . baerlocheri and F . pinnata are conspecific. A new specimen of P . cornigera provides additional information concerning leaf lobule, stylus and leaf cells. The fossil record and phylogenetic analysis of the liverworts recovered in mid-Cretaceous Burmese and Alaskan amber clearly show that Frullaniaceae have already accumulated some notable diversity in the Cretaceous, including the extant genus Frullania with three species and the extinct monotypic genus Protofrullania from mid-Cretaceous Burmese amber and probably also the extinct monotypic genus Kaolakia from mid-Cretaceous Alaskan amber.